PENGARUH PERSEDIAAN BARANG DAGANG TERHADAP PENJUALAN PADA PT. INFO OPTIMA KOMPUTASI TANGERANG - Nurlaelah Nurlaelah (Sekolah Tinggi Ilmu Ekonomi La Tansa Mashiro, 2022)
This study aims to produce information in the form of a more in-depth explanation of the effect of merchandise inventory on sales. And obtain resuls from processed data about how much influence the inventory of merchandise on sales.The research method used in this study data obtained both quantitatively and qualitatively was investigated using descriptive methods, namely in the form of field studies and direct surveys through interviews and observations in the form of direct observation. The sample used in this study is merchandise inventory report data and sales report data for 36 months.Based on calculations with a simple linear regression equation between X anad Y is Y = 895.502,820 + 0,642X …..e, if the inventory is zero then sale is -= 895.502,820, if the inventory increases one unit then sales increase by 0,642. While the results of the Hypothesis Testing, obtained merchandise inventory variables have a sig value0.05 means significant. While tcount = 11,631 and ttable = 2,032.Then the Merchandise Inventory variable has a positive and significant effect on Sales. And based on the correlation coefficient analysis, the value of r = 0.894 is obatained, which means that there is a strong relationship between the inventory of goods and Sales. While the results of KD (R^2) = 79,9%. This means that 79,9% of the independent variabels, namely merchandise inventory can explains the dependent variable, namely Sales. While the remaining 20,1% is explained by other factors not examined by this study